Teks Satua Crukcuk Kuning, I Pucung dan I Botol Teken I Samong: Analisis Penokohan dan Amanat - Bonytha Purwaningrat, Ni Luh Putu (Humanis, 2015)
This research was discused about the text of Satua Crukcuk Kuning, I Pucung and I Botol teken I Samong with characterizations and message in the story analysis. The aims of this analysis are to describe how the author act the characters and describing the message in the story that contained in text of Satua Crukcuk Kuning, I Pucung and I Botol teken I Samong. This research used the structural theory. This theory was used by many opinions of literary experts such as : Ratna, Endraswara, Teeuw, and Nurgiyantoro. The methods and technic that use in this research was devided into three steps there are, 1) provision data step, using reading method, helped with translation technic and writing technic 2) analysis data using qualitative method helped with using analytic descriptive technic 3) presentation the result of the analysis using informal method helped using deductive-inductive technic. The results that we get from this research are the revealed narative structure that consist of incident, plot, characters, background theme, and message in the story. Besides that, this research can be revealed the characterizations aspect that was describing based on (fisiologic, sociologic and pshicologic) and the characterizations (analytic, dramatic and combined). The message in the story that consist of Satua Crukcuk Kuning, I Pucung and I Botol teken I Samong are about falseness, brotherhood, attitude good moral, good leadership and help each other.
Keywords: satua, structure, characterizations and message in the story